Mag men : fifty years of making magazines - Bernard, Walter, 1937-; Glaser, Milton (Columbia University Press, 2019)
"For more than fifty years, Walter Bernard and Milton Glaser have revolutionized the look of magazine journalism. In Mag Men, Bernard and Glaser recount their storied careers, offering insiders' perspective on some of the most iconic design work of the twentieth century. The authors look back on and analyze some of their most important and compelling projects, from the creation of New York magazine to redesigns of such publications as Time, Fortune, Paris Match, and The Nation, explaining how their designs complemented a story and shaped the visual identity of a magazine"--